Strategi Optimalisasi Pelayanan Sirkulasi Dengan Pendekatan Model Harapan Sosial: Studi Pada Perpustakaan UNRI Pascagangguan Alam - Ajir Ajir; Evi Susanti; Yasin Setiawan (Jurnal Gema Pustakawan, 2022)
This study aims to find out the description of optimizing circulation room repairs after infrastructure damage due to natural disturbances. This research uses the Research And Development (R&D) method. This analytical method is widely used in research to develop an innovative product, including it can be used in optimizing circulation services. Technically, this concept is a development research methodology conducted at the CRDS (Center for Research and Development Strategy) in Japan. A brief description of this concept is the research stages depicted through the diagram "Social expectations research phase". Based on the results of the research that has been carried out, it is obtained an illustration that natural disturbances in the form of animal disturbances have caused damage to the upper part of the library, especially in the circulation space section. As a result of this incident, there was damage to the circulation space infrastructure which had to be handled immediately. The final results of the study show that users are satisfied with the development carried out, so it can be concluded that circulation services after damage to natural disturbance infrastructure have been running optimally.